A Multiplierless DC-Blocker for Single-Bit Sigma-Delta Modulated Signals. (19th November 2006) - Sadik Sadik, Amin Z. Amin Z.; Hussain Hussain, Zahir M. Zahir M.; O'Shea O'Shea, Peter Peter
Abstract : The DC content in single-bit domain is both undesirable and hard to remove. In this paper we propose a single-bit multiplierless DC-blocker structure. The input is assumed to be sigma-delta modulated bitstream. This DC-blocker is designed using a delta modulator topology with a sigma-delta modulator (SDM) embedded in its feedback path. Its performance is investigated in terms of the overall signal-to-noise ratio, the effectiveness of DC removal, and the stability. The proposed structure is efficient for hardware realisation.